PENERAPAN MODEL PROJECT BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI ENERGI DI KELAS III SD BIREUEN - Juliana; Khairunnisak; Lissa Zikriana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve student learning outcomes, teacher and student activity, and student responses to the application of the Project Based Learning (PjBL) model on the topic of energy in Grade III of UPTD SD Negeri 3 Jangka. The type of research used is Classroom Action Research (CAR) with a research subject of 22 students. The results showed significant improvement in all measured aspects. Teacher activity increased from 85.6% in Cycle I to 97.2% in Cycle II, while student activity increased from 70.7% to 94.7%. Student learning outcomes also improved, with the completion percentage rising from 36.4% in Cycle I to 90.9% in Cycle II, and the class average score increasing from 63.6 to 87.3. In addition, as many as 95.2% of students gave a positive response to project-based learning. This study concludes that the Project Based Learning model is effective in improving IPAS (Natural and Social Sciences) learning outcomes on the topic of energy in elementary school.